Villa Dentista a dental holiday resort - Dela Fuente, Sarah Patricia G.; Rinen, Richard Martin (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
Dental Tourism has become a popular sub-sector of Philippine medical tourism. Although local dental clinics have begun offering tourism packages to address this growing sector, some needs have remained unanswered. These are the holiday needs of medical tourists. This study aims to design a development that provides for both the medical and holiday needs of a dental tourist in the Philippines. The project is Villa Dentista: A Dental Holiday Resort. It is located in Pililla, Rizal. A site mainly chosen for its rural setting that includes vistas of the mountains and Laguna de Bay. The topography of the site was a major concern but was mainly addressed by building along the slope. The development consists of three main buildings; a dental hospital, a hotel with villas and a spa-commercial building. Functionality (zoning and circulation) was the most important consideration. The design concept of the development is "smile". Applying this concept, the design aims to be warm and welcoming, open while establishing connections and aesthetically pleasing in the midst of its rural context. To provide a united a medical and holiday experience, a variety of outdoor amenities are provided including pools, playing courts, picnic grounds and a fish pond. To allow the development to merge with the site, design features are employed that utilized the site's natural features. These include balconies and scenic elevators for access to vistas, a curving roof to highlight the existing tree line and corridors as breezeways catching the wind. Lastly, to mere hospital and resort architecture, connections were provided via walkways and pathways, similar spatial layouts and repeated visual cues.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Medical tourism -- Philippines -- Pililia, Rizal